Pengembangan Booth Display Sebagai Upaya Promosi dan Pemasaran untuk UMKM Desa Bagor sebagai Penunjang Destinasi Wisata The New Kemukus, Sragen - Basnendar Herry Prilosadoso; Ditya Fajar Rizkizha; Rendya Adi Kurniawan; Isnawati Muslihah; Hening Laksani; Zahra Titania Magenta; Nauril Ni’ma; Krisna Adi Heryoga; Immanuel Abimanyu; M. Harun Rosyid Ridlo; Brilindra Pandanwangi; Ipung Kurniawan Yunianto; Yoga Prasetya Adi Nugraha; Ratna Susanti; Brillian Nur Diansari; Sri Murwanti; Nursiam (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
The New Kemukus religious tourist attraction, located in Sumberlawang District, Sragen, continues to be beautified. Once known for its negative stigma, it has now been transformed into a new tourist icon in Sukowati. The Sragen Regional Government has allocated a development budget and prepared a regional public service agency (BLUD) to manage Mount Kemukus. The New Kemukus area is located in the Bagor Village, Miri, Sragen, an agricultural village with social, cultural, economic, educational, health, and infrastructure conditions that support 18 MSMEs, such as processed food products, clothing, culinary, children's toys, and other businesses. Community empowerment is an economic development concept that encompasses community values to build a new perspective for the community towards themselves and their environment, which is people-centred, participatory, empowering, and sustainable. Several training sessions were conducted to improve products, both in terms of quantity and processing, as well as other managerial aspects. Based on observations, the problems faced by these MSMEs consist of two aspects, such as the lack of promotion and marketing skills through booth display arrangements to improve product marketing. This activity is in accordance with the Master Plan of PPM ISI Surakarta, focusing on the application of art and appropriate technology in PPM for engineering art-based technology applications aimed at applying art to diversify creative products. The mentoring activity method for promoting booth displays and marketing uses the Design Thinking method through the following stages: Define, Research, Ideate, Prototype, Select, Implementation, and Learn. The mandatory outputs of the PKM include a scientific article (submitted) in a Sinta-indexed journal, a presentation of the activity results, a Letter of Application of Science and Technology from the partner, as well as additional outputs in the form of activity publications in the mass media, and an intellectual property (KI) submission in the form of a booth stand design.